Parenting issues in educating children with adhd in the contex of inclusive education in Ukraine - Fert, Olha (Special Education, 2019)
The article deals with the most common mental disorders of children in Ukraine in the context of the current international classification. The role of heredity in the etiology of Attention Deficit Hyperactivity Disorder is noted. The issue of appropriate family upbringing for the purpose of full inclusion of the child with ADHD is raised. The progress of parents of children with ADHD in the process of family education with the support of non-governmental organizations is analyzed.